Pencak Silat as character education for Generation Z - Putri, Mas Fierna Janvierna Lusie; Agustin, Sonia; Rosmiati, Yatti; Rahayu, Yayuk Muji; Akhirudin, Akhirudin (Indonesian Research Journal in Education |IRJE|, 2026)
Pencak silat, a traditional Indonesian martial art, embodies educational values that foster character development and national identity. This study examines the role of pencak silat as a medium for character education among Generation Z in Pasirtanjung Village. The research employed a quantitative survey design involving 22 Generation Z participants actively engaged in pencak silat training. Data were collected using a Likert-scale questionnaire and analyzed using SPSS through validity, reliability, normality, linearity, and simple linear regression tests. The findings reveal that participation in pencak silat has a positive and significant influence on students’ patriotic attitudes (Sig. = 0.048 < 0.05). The regression analysis shows that pencak silat accounts for 18.1% of the variance in the development of patriotic character, while the remaining variance is attributable to other educational and social factors, such as family background, peer influence, and school environment. These results indicate that pencak silat activities can serve as an effective cultural-based educational approach to strengthen character education and nationalism among young people.